Analysis of the Effect of Work Competency and Employment on Performance Teaching Teachers in School Maitreyawira Deli Serdang - Eric Gunawan; Robin (Institute of Computer Science (IOCS), 2022)
The implementation of this study aims to determine and analyze the effect of work competence and work spirit on the teaching performance of teachers at the Maitreyawira Deli Serdang school. The total population used is 117 teachers and the sampling uses a saturated sample where all teachers will be used as research samples. The results showed that both partially and simultaneously work competence and work spirit had a significant influence on teacher teaching performance.